A ANALISIS DAN KAJIAN LITERATUR PEMANFAATAN BEESMART PEMBUATAN SOAL UJIAN SMAS KRISTEN WEEKAROU - YENIYATI TUWA RINGU (Lembaga Penelitian dan Pengabdian pada Masyarakat (LPPM) STMIK Global Informatika MDP, 2023)
Abstract Mid-Semester Exams (UTS) and Final Semester Exams (UAS) at SMAS Kristen Wee Karou, currently still carry out exams manually using paper and stationery. The conventional examination system that is carried out still has many weaknesses, including duplication and distribution of question papers which require costs and do not guarantee security, unlimited use of paper answer sheets. Inaccuracy in the time for administering and collecting exam answers, as well as checking answer sheets which takes quite a long time. SMAS Kristen Wee Karou needs to use a BeeSmart Computer Based Test application to assist in the process of managing exam questions so as to reduce the cost of printing exam questions, help the exam implementation process so that the exams are more structured, on time and reduce the use of paper and stationery, helping the examination process exam results, as well as helping provide information on exam results in a timely manner. The method for collecting data in this research is analyzing 10 previous research journals or literature reviews with 3 stages, namely planning, implementation and reporting. The result of this literature study is the Application of CBT (Beesmart) can solve problems that exist in the Learning Evaluation activity process at SMAS Kristen Wee Karou and can produce an assessment process that is objective, thorough, fast and accurate and can be used as a learning medium for conducting learning evaluations for teachers. Keywords: CBT, BeeSmart, Examination Questions